Energy and Entropy-Based Optimization of a Single-Stage Water–Lithium Bromide Absorption Refrigeration System. Issue 2 (22nd January 2016) - Samanta, Samiran; Basu, Dipankar N.
Abstract : Thermodynamic optimization of single-stage water–LiBr absorption system was performed earlier both from first- and second-law points of view. However, a realistic comparison between the two approaches is essential to identify the superior one. Hence a theoretical model is developed to optimize the absorption chiller for identifying conditions corresponding to maximum system coefficient of performance (COP) and minimum entropy generation rate. Optimum generator temperature for minimum entropy generation is found to be lower than that corresponding to maximum COP, with absorber having a dominant role in enhancing irreversibility in system. Optimal generator temperature decreases with increasing evaporator temperature and decreasing condenser temperature. Thus, it is possible to identify optimum value for any combination of condenser and evaporator temperature from both the energy and entropy points of view. Concerned contour maps are presented. Adoption of an entropy-optimized map is suggested, owing to higher sensitivity of entropy generation to the changes in condition compared to COP.